2022
DOI: 10.1155/2022/8411851
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Antidiabetic and Antihyperlipidemic Effects of 80% Methanolic Extract of the Lonchocarpus laxiflorus Leaves in Streptozotocin-Induced Diabetic Swiss Albino Mice

Abstract: Introduction. Diabetes mellitus (DM) is a chronic endocrine disorder that requires long-term treatment. In Ethiopian traditional medicine practice, plants have been provided with a vital role in fighting human and animal diseases since ancient times. The aqueous extract of Lonchocarpus laxiflorus (L. laxiflorus) leaves has been consumed for treating diabetes mellitus without confirming its safety and efficacy scientifically. This experiment aimed to evaluate the safety and antidiabetic efficacy of the leaf ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated the involvement of phytochemical compounds such as triterpenes [31,32], flavonoids [33][34][35], and tannins [36] for the management of diabetes. These compounds might act by several mechanisms such as enhancing insulin secretion [37] or regenerating insulinproducing pancreatic β-cell population in the islets of Langerhans [38][39][40]. Thus, H. sabdariffa extract may enhanced insulin secretion by stimulating the β-cell of the Langerhans islets of the pancreas as its also consists of flavonoids, phenols, and tannins.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the involvement of phytochemical compounds such as triterpenes [31,32], flavonoids [33][34][35], and tannins [36] for the management of diabetes. These compounds might act by several mechanisms such as enhancing insulin secretion [37] or regenerating insulinproducing pancreatic β-cell population in the islets of Langerhans [38][39][40]. Thus, H. sabdariffa extract may enhanced insulin secretion by stimulating the β-cell of the Langerhans islets of the pancreas as its also consists of flavonoids, phenols, and tannins.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that the hydroethanolic extracts of B. dalzielii and H. sabdariffa possessed hypoglycemic and hypolipidemic properties in alloxan-induced diabetic rats [ 13 , 14 ], notably through reducing blood glucose, improving glucose tolerance, and normalizing lipid profiles. These plants and their phytochemical compounds might act by several mechanisms, such as enhancing insulin secretion by stimulating the β-cell of the Langerhans islets or regenerating the insulin-producing pancreatic β-cell population in the islets of Langerhans [ 27 ]. We evaluated the antioxidant and anti-inflammatory properties of B. dalzielii and H. sabdariffa in alloxan-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%